Industrial training report: Corporate Information Technology department, 10th floor, Menara Naza, 115, Jln Raja Muda Abdul Aziz, Kg Baru, 50300, Kuala Lumpur - Azahari, Muhammad Zahir Reza (Bachelor of Science (Hons.) Record Management, 2015)
As all bachelor students are required to undergo industrial training for five months to complete their studies in Records Management, this report provide a detail description and overview on the activities and task done by trainee during the internship training. The internship was done at Corporate Information Technology Department and during the internship period, the trainee had been assign to variety of task. Each of the task assigned to the trainee such as setup network, setup hardware and software, and also asset management. The details on how the trainee carried out the special project was also included in this report. At the last chapter of this report, the trainee also state and share the outcome of the internship program, where the trainee was able to apply the knowledge gained during the classes, and also the new lesson the trainee learnt during the internship period.